Inappropriateness in composite laminate orthotropic elasticity formulations and numerical implementation of laminate elasto-plasticity within backward Euler integration algorithm - Ren, Rui; Zhang, ZhenDong; Zhong, Jianlin; Ma, Dawei (Composite structures, 2018)
Since contradictions occur among literatures in the mathematical formulation of composite lamina’s orthotropic elasticity and one doubt exists in one published paper’s numerical procedure about the iteration convergence during the Newton iteration for plastic strains based on backward Euler algorithm, the incorrect formulation of orthotropic elasticity is necessary to be modified and the convexity of yielding function respect to plastic consistency factor is recommended to be declared to guarantee the convergence of Newton iteration where the iterative results are more preferable based on converged state variables. This letter aims at modifying the published incorrect orthotropic elasticity model and perfecting the proposed implementation procedures of predicting composite laminate plastic deformation with the backward Euler algorithm and Newton iteration.